2020
DOI: 10.1111/jog.14555
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin promotes angiogenesis by activating the Jagged1/Notch2/VEGF pathway in preeclampsia

Abstract: Aim Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor (GHSR), has been found to be involved in the regulation of blood pressure; however, its effects in preeclampsia (PE) and the potential underlying mechanism remain poorly understood. In this study, we aimed to investigate the correlation between ghrelin and PE and reveal the possible mechanism underlying any relationship. Methods The levels of ghrelin and VEGF in the plasma of 6 early‐onset PE (EOPE), 6 late‐onset PE (LOPE) and 12 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
(48 reference statements)
3
13
0
Order By: Relevance
“…Interestingly, one study demonstrated that while in early onset preeclampsia (<34 weeks) ghrelin was reduced, it was increased in late onset preeclampsia [218]. Variations of ghrelin levels throughout pregnancy could be a reason while in contrast to the data displayed above there are also reports of increased circulating ghrelin levels in pregnancy-induced hypertension [213] and in mild and severe preeclampsia compared to healthy controls [216].…”
Section: Pregnancy-induced Hypertension and Preeclampsiamentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, one study demonstrated that while in early onset preeclampsia (<34 weeks) ghrelin was reduced, it was increased in late onset preeclampsia [218]. Variations of ghrelin levels throughout pregnancy could be a reason while in contrast to the data displayed above there are also reports of increased circulating ghrelin levels in pregnancy-induced hypertension [213] and in mild and severe preeclampsia compared to healthy controls [216].…”
Section: Pregnancy-induced Hypertension and Preeclampsiamentioning
confidence: 97%
“…The extent of decrease of ghrelin in PCOS is supposedly depending on body weight and severity of PCOS [201,204], with an increase of ghrelin after treatment-induced normalization of hyperandrogenemia [201,205]. Secondly, observations that ghrelin was reduced in early onset preeclampsia, while it was increased in late onset preeclampsia [218], could explain why some studies report increased ghrelin in pregnancy-induced hypertension [213] and in mild and severe preeclampsia [216], while others describe reduced circulating ghrelin in preeclampsia [215,217]. Thirdly, a majority of studies in GDM observed decreased circulating ghrelin in patients compared to controls [64,65,88,219], with no difference 15 days after delivery in ghrelin serum between women with GDM and without diabetes [64], indicating a normalization with decreased disease activity.…”
Section: Ghrelin's Role In Reproduction-related Health Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In preeclampsia, a known complication of pregnancy, ghrelin secretion is increased, and serum ghrelin levels have been reported to correlate negatively with blood pressure (55,56). It has been suggested that this is because ghrelin improves endothelial function by enhancing angiogenesis through the Jagged1/Notch2/VEGF pathway (57).…”
Section: Effects Of Ghrelin On the Cardiovascular Systemmentioning
confidence: 99%
“… 27 Accordingly, various interventions to restore the angiogenic balance in preeclamptic pregnancies have been found to improve maternal and neonatal outcomes. 28 Using the first trimester of human placental villous explants, it has been shown that 2-methoxyestradiol may act by modulating vascular endothelial growth factor receptors (VEGFR-2). It was shown that exposure of placental villous explants to hypoxia produced preeclampsia-like features, including an increase in soluble fms-like tyrosine kinase-1 (antiangiogenic factor).…”
Section: Preclinical Studies Showing the Role Of Estrogen In Preeclampsiamentioning
confidence: 99%